2002
DOI: 10.1017/s1431927602105629
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Si in a W matrix Using Diffraction Contrast in the TEM

Abstract: The practice of using a Si based gas prior to W deposition is a process used within the semiconductor industry to aid in uniform and continuous filling of interlevel interconnects. SIMS has been effectively used to determine the concentration of Si in the bulk of a W nucleation layer formed during a blanket deposition. RBS has also been employed to evaluate the W:Si ratio in the same nucleation layer. Such techniques have proven effective in the detection of low levels of Si in W; however, the lateral spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Redeposition of sputtered atoms has also been reported as a result of FIB milling [4]. The propensity for redeposition increases when FIB milling is performed in a confined and/or a high aspect ratio trench, or when FIB conditions are used that contribute to factors that increase the sputtering rate (e.g., using a higher beam current) [5]. Observations have shown that FIB milling with Ga at an energy of 30 keV will produce amorphization damage along a Si side-wall that is ~ 28 nm thick and up to 20 wt% Ga may be present within the damage region [6].…”
mentioning
confidence: 99%
“…Redeposition of sputtered atoms has also been reported as a result of FIB milling [4]. The propensity for redeposition increases when FIB milling is performed in a confined and/or a high aspect ratio trench, or when FIB conditions are used that contribute to factors that increase the sputtering rate (e.g., using a higher beam current) [5]. Observations have shown that FIB milling with Ga at an energy of 30 keV will produce amorphization damage along a Si side-wall that is ~ 28 nm thick and up to 20 wt% Ga may be present within the damage region [6].…”
mentioning
confidence: 99%